Unknown quantity a real and imaginary history of algebra - Derbyshire, John (Plume, 2007)
Gives form to the beauty and mystery of algebra, the most abstract of mathematical disciplines, in a reference that presents a cast of extraordinary historical characters who, through the centuries and across the world, played a role in the genesis of algebra.
Keywords: Geschichte; Geschichte Anfänge-2000; Algebra - History; Algebra -- History; Algebra, Abstract -- History; Algebra, Universal -- History; Equations -- History; Geometry, Algebraic -- History; Algebra; Algebraische Struktur